RAPID UPPER LIMB ANALYSIS IN ERGONOMIC RISK FACTORS AMONG PHOTOGRAPHERS. - N., SENTHIL KUMAR; S., SENTHIL KUMAR; VANKUMARJ, SARA; SRINIVASAN, VIGNESH; P. S., VIKRAM ADHITYA; H., JANANI (Turkish Journal of Physiotherapy Rehabilitation, 2021)
PURPOSE: A typical photographer's posture is with upper body forward, shoulders rolled in, and neck bent forward with chin extended. When less attention is paid to the physical damage caused by holding a certain position over time causes holding injuries technically called excessive positioning injuries. Swelling and heat in joints, physical stiffness and discomfort, headaches, jaw pain, and chronic neck or low back pain are all signs of excessive positioning injuries. The aim of this study is rapid upper limb analysis in ergonomic risk factors among photographers. METHODS: A convenient samples of twenty male photographers were taken for this study. Photographers were asked to fill the questionnaire to identify the musculoskeletal disorders during the photo-shoots. It is analysed by rapid upper limb analysis (RULA) and ergonomic risk factors noted. The outcome measure used in this study is RULA (rapid upper limb analysis). RESULTS:The results shows that high ergonomic risk factors in shoulder and neck region due to awkward positions and repeated strain over the neck and shoulder. Photographers in the current study adopted awkward postures and had high ergonomic risk levels when using their camera. CONCLUSION:It was found that prolonged occupational hazard and maintaining awkward positions were the main reasons for musculoskeletal disorders among photographers.